2020
DOI: 10.1101/2020.11.08.373167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resting state brain signal complexity of young healthy adults reflects genetic risk for developing Alzheimer’s Disease

Abstract: The e4 allele of the APOE gene is strongly associated with impaired brain functionality and cognitive decline in humans at older age. It is controversial whether and how the APOE e4 allele is affecting brain activity among young healthy individuals and how such effects may contribute to individual differences in cognitive performance. Signal complexity is a critical aspect of brain activity that has been shown to be associated with brain function. In this study, we analyzed multiscale entropy (MSE) of EEG sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Other studies on brain signal entropy in resting-state fMRI also showed substantial associations with gc (Saxe et al 2018). Moreover, information from cortical entropy profiles effectively predicted several cognitive abilities in a recent study by Li et al (2020).…”
Section: Brain Signal Complexity (Bsc) As a Neural Marker Of Creative...mentioning
confidence: 72%
See 2 more Smart Citations
“…Other studies on brain signal entropy in resting-state fMRI also showed substantial associations with gc (Saxe et al 2018). Moreover, information from cortical entropy profiles effectively predicted several cognitive abilities in a recent study by Li et al (2020).…”
Section: Brain Signal Complexity (Bsc) As a Neural Marker Of Creative...mentioning
confidence: 72%
“…This is the reason for only calculating MSE in this task up to time-scale 10. As systematically illustrated by Li et al (2020), the reliability of MSE decreases with the decreasing length of the time series. Thus, for these rather short time series, a higher-scale MSE would not satisfy these reliability expectations.…”
Section: Mse Computation Using the Eeg Signals Acquired During The Ve...mentioning
confidence: 87%
See 1 more Smart Citation